PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA GURU TETAP DI SMK MERDEKA BANDUNG - mahmudah, Ai Noer Millah (2016)
Penelitianinidilakukan di SMK Merdeka Bandung. Permasalahan yang menjadikajiandalampenelitianiniadalahbelumoptimalnyakinerja guru dalampembelajaran, meliputikomitmendalammengajar, menguasaimateri ajar, kedisiplinandankreatifitasdalammengajardankerjasamadengansekolah. Fokuskajiannyadiarahkanpadafaktor-faktor yang mempengaruhikinerja guru. Budayaorganisasidanmotivasimerupakanfaktor yang didugamemilikipengaruhterhadapkinerja guru. Olehkarenaitu,penelitianmengkajitigavariabelyaitubudayaorganisasi (X1), motivasi (X2) dankinerja guru (Y). Penelitianinimenggunakanmetode survey. Teknikpengumpulan data menggunakanangket. Respondenadalah gurutetap SMK Merdeka Bandung sebanyak32 orang. Teknikanalisis data menggunakananalisisregresi. Hasilanalisis data menunjukkanbahwabudayaorganisasiberadapadakategorikuat, motivasiberadapadakategoritinggi, dankinerja guru tetap di SMK Merdeka Bandung beradapadakategorisangattinggi. Berdasarkanhasilanalisisregresi, diperolehhasilbahwabudayaorganisasidanmotivasibaiksecaraparsialmaupunsimultanmemilikipengaruh yang positifdansignifikanterhadapkinerja guru.;-- This research was conducted at The Vocational High School Merdeka Bandung. The issue became a study in this research is having not optimal teachers performance in the learning such as commitment in teaching, master of teaching materials, discipline and creativity in teaching and cooperation with the school. Focus directed at factors that influenced teacher performance. Organizational culture and motivation are factors that thought to have influence on the teachers performance. Therefore the study examines three variabels, namely (X1) organizational culture, motivation (X2) and teachersperformance (Y). This research used survey method. Data collection techniques used question form. The respondents were teachers of The Vocational High School Merdeka Bandung as many as 32 people. The data technique analyzed using the regression. The result of the data analysis revealed that organizational culture included in strong category, motivation in high category, meanwhile teachers performance at The Vocational High School Merdeka Bandung included in very high category. Based on the analyzed of regression, the result revealed that organizational culture and motivation both partially and simultaneously, has the positive and significant influence toward teacher performance.